The Effect of Customer Empowering Behaviors on Service Performance in Hospitality Industry - Öksüz, Merve (International Journal of Contemporary Economics and Administrative Sciences, 2021)
Customers’ actions may encourage and motivate employees to make decisions about successful service delivery which is called customer empowering behaviors (Dong, Chuang, Liao, Zhou & Campbell, 2015). This article aims to explain antecedents of customer empowering behaviors which have impacts on employee absorption and customer service performance in the service industry. In this study, a multilevel conceptual model is used and suggests that customer empowering behaviors will be efficient on customer service performance through fostering job engagement. Quantitative research method is used by collecting questionnaires from 421 frontline employees who work either at the reception desk or guest relations in hotels with 4 and 5 stars in the South and South Western districts of Turkey. SEM and HLM were used to analyze collected data in research. The results indicate that customer empowering behaviors play a vital role that affects customer service performance through promoting employee absorption, however, customer complexity has not any significant effect on relationships between customer empowering behaviors and employee absorption and customer service performance.